Genetic algorithm optimization for highly efficient solar thermal absorber based on optical metamaterials. (September 2021) - Cai, Haoyuan; Sun, Yi; Liu, Jing; Wang, Xiaoping
Highlights: Absorber has a broadband absorption (>97.8%) from 300 nm to 2000 nm. The optical performance of absorber is optimized by RCWA and GA methods The solar thermal conversion efficiency of the absorber can reach 91.7% and 85.17%, at 373.15 K and 1000 K, respectively. The physical mechanisms responsible for nearly perfect absorption are discussed. Abstract: A near-ideal solar thermal absorber is designed theoretically in this paper. The absorber consists of 2-dimensional W square grating arrays, which are embedded in SiO2 layer that is deposited on a W/SiO2 /W waveguide. The optical performance of this metamaterial-based absorber is optimized using a genetic algorithm (GA), and its average absorption is 97.8% between 300 nm to 2000 nm. The total emittance is calculated to be 4.18% and 19.65% in the 0.3 µm - 20 µm spectral range, at 373.15 K and 1000 K, respectively. Thus, the solar thermal conversion efficiencies of the metamaterial absorber are up to 91.7% and 85.17%, at 373.15 K and 1000 K, respectively. The finite difference time domain (FDTD) indicates that broadband absorption characteristics result from the coupling effects associated with the gap plasmon resonance, localized surface plasmons (LSPs), and magnetic resonance. An inductor-capacitor (LC) circuit model is used to predict the excitation wavelength of the magnetic resonance. In addition, the highly-efficient solar thermal absorber is demonstrated to be insensitive on angle of incidence. This means the new architecture can be used as an efficient wavelength-selective absorber in solar thermal systems.